2014
DOI: 10.1016/j.jnutbio.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane reduces vascular inflammation in mice and prevents TNF-α-induced monocyte adhesion to primary endothelial cells through interfering with the NF-κB pathway

Abstract: Sulforaphane, a naturally-occurring isothiocyanate present in cruciferous vegetables, has received wide attention for its potential to improve vascular function in vitro. However, its effect in vivo and the molecular mechanism of sulforaphane at physiological concentrations remain unclear. Here, we report that a sulforaphane concentration as low as 0.5 μM significantly inhibited TNF-α-induced adhesion of monocytes to human umbilical vein endothelial cells (HUVECs), a key event in the pathogenesis of atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 53 publications
2
59
0
Order By: Relevance
“…SFN also has a strong anti-inflammatory effect in many tissues. Nallasamy et al (18) have found that dietary supplementation of SFN prevents TNF-␣-induced vascular endothelial inflammation of mice. Besides, Nguyen et al (19) have discovered that SFN reduces inflammatory responses of cardiopulmonary bypass.…”
Section: Inflammation Is Widely Distributed In Patients Withmentioning
confidence: 99%
“…SFN also has a strong anti-inflammatory effect in many tissues. Nallasamy et al (18) have found that dietary supplementation of SFN prevents TNF-␣-induced vascular endothelial inflammation of mice. Besides, Nguyen et al (19) have discovered that SFN reduces inflammatory responses of cardiopulmonary bypass.…”
Section: Inflammation Is Widely Distributed In Patients Withmentioning
confidence: 99%
“…However, the contributory role of SAHA on HDAC isoforms to KLF2 upregulation need to be further elucidated. Although we have shown that SAHA reduces monocyte adhesion under static conditions, it would be important to validate the antiadhesive effects of SAHA in a more physiologically relevant model by applying shear flow and TNFα 45, 46. We also recognize that atherosclerosis is a complex, chronic inflammatory disease with the functional interplay among different cell types 47.…”
Section: Discussionmentioning
confidence: 96%
“…This observation is in agreement with and confirms Marikovsky's and Batya's application to use thiram as a component of some pharmaceuticals useful as an anti-inflammatory agent 11 . In the literature, there are many proofs that compounds with pro-oxidative activity restrain inflammatory response in cells [67][68][69][70][71] . Such paradoxical effects are also known among antioxidants, e.g.…”
Section: Discussionmentioning
confidence: 99%